Near infra-red light treatment of Alzheimer’s disease - Mengmeng Han; Qiyan Wang; Xue Wang; Yuhui Zeng; Yong Huang; Qingqiang Meng; Jun Zhang; Xunbin Wei (Journal of Innovative Optical Health Sciences, 2018)
Alzheimer’s disease (AD) is a chronic neurodegenerative disease. The symptoms include memory and spatial learning difficulties, language disorders, and loss of motivation, which get worse over time, eventually ending in death. No effective treatments are available for AD, currently. Current treatments only attenuate symptoms temporarily and are associated with severe side effects. Near infra-red (NIR) light has been studied for a long time. We investigated the effect of NIR on AD using a transgenic mouse model, which was obtained by co-injecting two vectors carrying AD mutations in amyloid precursor protein (APP) and presenilin-1 (PSEN1) into C57BL/6J mice. The irradiation equipment consisted of an accommodating box and an LED array. The wavelength of NIR light emitted from LED was between 1040nm and 1090nm. The power density delivered at the level of the mice was approximately 15mW/cm2. Firstly, we treated the mice with NIR for 40 days. Then, the irradiation was suspended for 28 days. Finally, another 15 days treatment was brought to mice. We conducted Morris water maze and immunofluorescence analysis to evaluate the effects of treatment. Immunofluorescence analysis was based on measuring the quantity of plaques in mouse brain slices. Our results show that NIR light improves memory and spatial learning ability and reduces plaques moderately. NIR light represents a potential treatment for AD.